2019
DOI: 10.1002/cam4.1949
|View full text |Cite
|
Sign up to set email alerts
|

The discovery and characterization of K‐563, a novel inhibitor of the Keap1/Nrf2 pathway produced by Streptomyces sp

Abstract: Keap1/Nrf2 pathway regulates the antioxidant stress response, detoxification response, and energy metabolism. Previous reports found that aberrant Keap1/Nrf2 pathway activation due to Kelch‐like ECH‐associated protein 1 (Keap1) mutations or Nuclear factor E2‐related factor 2 (Nrf2) mutations induced resistance of cancer cells to chemotherapy and accelerated cell growth via the supply of nutrients. Therefore, Keap1/Nrf2 pathway activation is associated with a poor prognosis in many cancers. These previous findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Of note, K-563 abrogated the expression of NRF2 target genes such as GCLC, GCLM, AKR1C1 (reductase family 1 member C1), ME1, NQO1 and TXNRD1 in A549 NSCLC cells and in the human gallbladder cancer (GBC) cell line TGBC24TKB, without altering the NRF2 protein levels, its ARE-binding ability, or its nuclear localization. As a result, K-563 promoted ROS accumulation and synergized with either Cisplatin or Etoposide in A549 NSCLC cells, suppressing also cell proliferation in GBC cells (TGBC24TKB) without affecting normal human lung cells (BEAS-2B) [337]. In the context of hematologic tumors, Zhang et al, identified 4f, a pyrazolyl hydroxamic acid derivative with potent antineoplastic effects in human THP-1, HL60 and U937 AML (acute myeloid leukemia) cells.…”
Section: Natural and Synthetic Compounds Blocking Nrf2 Pathway By Stimentioning
confidence: 99%
“…Of note, K-563 abrogated the expression of NRF2 target genes such as GCLC, GCLM, AKR1C1 (reductase family 1 member C1), ME1, NQO1 and TXNRD1 in A549 NSCLC cells and in the human gallbladder cancer (GBC) cell line TGBC24TKB, without altering the NRF2 protein levels, its ARE-binding ability, or its nuclear localization. As a result, K-563 promoted ROS accumulation and synergized with either Cisplatin or Etoposide in A549 NSCLC cells, suppressing also cell proliferation in GBC cells (TGBC24TKB) without affecting normal human lung cells (BEAS-2B) [337]. In the context of hematologic tumors, Zhang et al, identified 4f, a pyrazolyl hydroxamic acid derivative with potent antineoplastic effects in human THP-1, HL60 and U937 AML (acute myeloid leukemia) cells.…”
Section: Natural and Synthetic Compounds Blocking Nrf2 Pathway By Stimentioning
confidence: 99%
“…In vivo experiments on xenograft mice with A549 cells showed that K563 effectively suppressed the KEAP1/NRF2 signaling pathway within lung cancer tumors. [306].…”
Section: Targeting Of Nrf2 Signaling To Fight Chemo-resistance: Nrf2 ...mentioning
confidence: 99%
“…In addition, the inhibitor K-563 produced by Streptomyces sp. is able to reduce the production of GSH by inhibiting the Keap1-Nrf2 pathway [ 142 ]. Both inhibitors raise the sensitivity of tumour cells by adjusting glucose and glutamine catabolism.…”
Section: Role Of Ros In Radiosensition and Chemosensitionmentioning
confidence: 99%